Impact of Technological Innovation on Performance of Manufacturing Firms in Switzerland - Sukumar, Seferovic Haris; Vargas , Agarwal Okafor; Mondal, Sommer Yann (Journal of Strategic Management, 2022)
Innovation is using knowledge to develop something with new economic value. Technological innovation is vital for firms to drive their growth, create value for the firm and its clients, and develop a competitive advantage. Thus, the study sought to examine the impact of technological innovation on the performance of manufacturing firms in Switzerland. The study adopted the descriptive research design. The target population was 658 respondents from Eastman Chemical International GmbH Zoug. The sample size was 249, which was determined using the Yamane formula. The study used questionnaires to collect the data. The analysis of the data was done using inferential statistics. The study found that technological innovation is positively and significantly related to performance (β=0.684, p=0.005). The research concluded that technological innovations influence the performance of Eastman Chemical International GmbH Zoug. Technological innovation brings benefits. It increases productivity and brings better goods and services that improve the overall standard of the goods and services produced by an organization. The power of service innovation in helping the firm to keep and expand its competitive position is indisputable. It is noted that technological innovation technique is vital for firms to drive their growth, create value for the firm and its clients, and develop a competitive advantage. The research recommends that for the firms to realize higher performance, they should adopt technologically innovative strategies. Firms should aim to ensure service range expansion, replacement, enhancement, repositioning and new service introduction to enable the firm to be much more effective, grow quicker, invest more and gain more competitiveness. The aspect of technological innovation should be given an upper hand in any organization if higher performance is to be achieved. Keywords: Technological innovation, performance, manufacturing firms, Switzerland